(untitled) (Journal of the College of Basic Education, 2023)
The issue of youth is one of the vital topics, and it receives the attention and attention of many who are interested in the affairs of education and leadership, because youth have the greatest role in the growth and development of society, and they also represent a huge energy for work, and a force capable of bringing about change in various fields of life.The youth stage is one of the most important and dangerous stages of growth. Because it is characterized by many characteristics and advantages, and physiological, psychological and mental changes, and this stage differs from childhood and adolescence and is directly related to the stage of adulthood.